Ethnobotanical studies on medicinal plants used by sugalis of yerramalais in kurnool district, Andhra Pradesh, India - S.Kahleel Basha; G.Sudarshanam (International Journal of Phytomedicine, 2010)
In India, the use of different parts of several medicinal plants to cure specific ailments has been practiced since ancient times. Ehanobotanical studies were carried out to collect information on the use of medicinal plants by the tribal community (Sugalis) who live in the forests of Yerramalais of Kurnool district, Andhra Pradesh, India. The present paper deals with identification of 40 medicinal plants, with local names used by Sugalis for different diseases. The information about different types of medicinal plants used by them for various diseases recorded orally by interviewing the elders, Vaidyas (doctors) of that tribe by visiting their habitats called Thandas. Collected plants are stored in the Departmental Herbarium of Osmania College, Kurnool. Most of the medicinal plants are taken in as roots, tubers, stem and leaves, are taken orally with or without combination of other plants, external applications like paste, fumigation. Most of plants used by them are Herbs (42%), shrubs (20%), Trees (33%).and Climbers (5%) The most striking feature of tribal life is their simplicity. The forest is able to provide them with everything. Professionally they are peasants, food-gatherers, hunters, small farmers, and, nomads. Sugalis use medicinal plants mainly for viral fevers, skin deceases, snake & scorpion bites and stomach problems. It is observed that the urban educated people are more aware of good effects of herbal medicine over allopathic medicine than the rural people. Due to the degraded forests and depleted resources, they are migrating to urban areas for livelihood. So there is a danger of losing knowledge of medicinal plants for human welfare. Hence there is an urgent need to document and popularize the value of herbal medicine among the rural people through Vana Samrakhak Samithi and other agencies.